Social participation of students with special educational needs in inclusive elementary schools - Marlina , Marlina; Kusumastuti, Grahita (Special Education, 2019)
This article examines the social participation of students with special needs in four aspects, namely friendship, interaction, social self-perception, and peers acceptance. This study discuss about the social participation of students with special needs in inclusive school. This research is descriptive quantitative and the relationship between the four aspects of social participation. The subject of this research are students with special needs and regular students in ten inclusive elementary school, Padang. The social self-perception was measured with three aspects such as the Self-Perception Profile for Children, The Self-Description Questionnaire and Peer Social Acceptance The results showed that the majority of students with special needs have a satisfying level of social participation. However, if compared with their peers (regular students), students with special needs are more likely to have difficulties on social participation. In general, students with special needs have fewer friends and have less cohesive friendship than their peers. In addition, students with special needs have less interaction with peers, more interaction with the teacher, and less accepted by their normal peers. Social self-perception of students with special needs and regular students are no different. There is no significant differences in social participation in both groups.